STRATEGI PELAYANANROOM ATTENDANT DALAM MENINGKATKAN OCCUPANCY HOTEL PUSAKO BUKITTINGGI - S.STPar, MM, ROZI YULIANI, (Menara Ilmu, 2017)
Hotel PusakoBukittinggi is a 4-star hotel (****) which are on the road Soekarno-Hatta7 Bukittinggi.As the development of the tourism sector, making someone wants to travel bothdomestically and abroad. This would make someone want to get a comfortable resting place inaccordance with their wishes. Therefore, the hotel will be competing to provide the bestservice for the guests such as Pusako Bukittinggi hotel. The success can be seen from a hotelroom occupancy rate and this could be a good image for the hotel. This study aims todetermine the service strategy room attendant to room occupancy levels in accordance withthe expectations of guests.This research uses descriptive qualitative research. The population or sample of thestudy include housekeeping manager, supervisor and room attendant located at the hotelPusako Bukittinggi, totaling 13 respondents.The results showed that the occupancy rate of hotel rooms inPusakoBukittinggi belowthe expected target for what is offered to guests not in accordance with what you got guests.Inaddition, services provided by the room attendant unfavorable, such as discipline accesoriesroom attendant who wore a necklace when working, rooms were still dusty and guest suppliesare not equipped in the room. And also the current strategy needs to be socialized by thehousekeeping manager to subordinate to the increase in hotel occupancy PusakoBukittinggi.Based on the research results it can be suggested that the management of the hotelPusakoBukittinggi provides trainning periodically for all employees especially the roomattendant to improve services in order to achieve occupancy that is targeted by the hotel,minimize complaints from guests and hoped that room attendant can perform their duties andresponsibilities as good as possible.Keyword: Strategy, Room Attendant, Occupancy